All-natural, sustainable laminated composites from bacterial cellulose and wheat flour paste. (October 2022) - Li, Zhaoqian; Wang, Mengling; Wu, Bo; Luo, Qingping; Liu, Xun; Pei, Chonghua
Abstract: Biocomposites from renewable resources have shown promising applications instead of traditional composites. However, the mechanical properties of existing biocomposites have limited their application in structural materials. In this paper, inspired by the layered microstructure of biological materials, bacterial cellulose (BC)/wheat flour (WF) laminated composites completely derived from renewable resources were fabricated by layer-by-layer assembly using WF paste as a green adhesive. The results reveal WF paste can bond well with the BC layer and exhibit good interfacial compatibility with BC nanofibers, which endows the laminated composites with excellent mechanical performance, showing potential applications in various fields.